Penerapan Metode Talking Stick pada Pembelajaran Bahasa Arab untuk Meningkatkan Penguasaan Mufrodat Siswa Kelas VII E MTs Islam Ngruki Sukoharjo Tahun Ajaran 2023/2024 - Miftahul Jannah Kurnia Sari; Anis Budiriyanto (Thulabuna: Jurnal Pendidikan Bahasa Arab, 2019)
This research is motivated by the lack of effective and enjoyable teaching methods in Arabic language learning, which results in low student interest and causes students to be less enthusiastic about learning Arabic. The research method used is descriptive qualitative research, with the research subjects being 25 seventh-grade E students of MTs Islam Ngruki. Data collection techniques included observation, interviews, and documentation. The data analysis technique in this study consists of three stages: data reduction through the researcher's observations and learning evaluation results, data presentation by describing the obtained data, and drawing conclusions. From the research findings and discussion, it is known that there is an improvement in students’ learning evaluation results when using the Talking Stick method. The application of the Talking Stick method encourages activeness, time efficiency, and increases motivation in learning Arabic among class VII E students of MTs Islam Ngruki. This can be seen from the increase in the class average score, which reached an average of 91.76, and the number of students who achieved a passing grade. In the evaluation process, 20 out of 25 students obtained a "Pass" grade with a very satisfactory score (above 90). However, every method has its advantages and disadvantages. The advantages of the Talking Stick method include enhancing students' creativity, memory, and comprehension. Meanwhile, its drawback is that it is less effective when applied to texts that are too long or narrative-heavy.